Pendidikan dalam Proses Kebudayaan yang Multikultural di Indonesia - Rima Trianingsih (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2017)
The important role of education is how to shaping the human personality. Experts behaviorists and psychoanalyst see of education in culture. Some education experts explained that educational process is the process of cultural transmission. The educational process also normative, not blind value. Cultural differences and ethnic multicultural influence in the educational process. The psychological basis of multicultural education places emphasis on the development of a greater self understanding, positive self concept, and pride on his personal identity. Multicultural education raised the core values that are derived from the principle of human dignity, justice, equations, freedom, and democracy.